ANALYSIS OF FACTORS AFFECTING THE SUPPLY OF RAW MATERIALS IN BREAD PRODUCER MSMES IN SOUTH TANGERANG CITY - Edmon Daris; Iwan Aminudin; Sekar Alifia Farahheny (AGRIBUSINESS JOURNAL, 2021)
The existence of inventory aims to prevent production activities from being delayed and running smoothly.  In raw goods inventory activities, obstacles are felt jointly by bread producers in South Tangerang City which are caused by the lack of capital in bread MSME entrepreneurs. The perceived lack of capital has an impact on the process of inventorying raw materials for production. Then another thing that must also be faced from the lack of capital according to a survey conducted on Bread MSMEs in South Tangerang City in the form of raw material prices and the availability of space for raw material storage so that production can run smoothly without any significant delays. This study aims to (1) analyze the influential factors in raw material inventory and (2) how much these factors affect raw material inventory, especially in bread producer MSMEs in South Tangerang City.The result of this study is that 3 variables that affect the supply of raw materials, namely capital, raw material prices, and warehouse costs. On the capital variable, the t-test showed a noticeable influence between the capital variable and the raw material inventory at a confidence level of 99.9%. This is because if the capital is not owned by the company, of course, the company cannot carry out its production activities.  Then the second variable is the price of materials which has a noticeable influence on the confidence level of <75%. In the third variable, warehouse costs also have a noticeable influence on raw material inventory with a confidence level of 80%.  In other words, the variable that most affects the supply of raw materials is the capital variable.